The Geometric Representations in an Interactive Geometry Textbook for Primary Education - Monge Madriz, Carlos Alberto (2024)
The project “Eveprim 3.1: An Interactive Geometry Resource for Third-Grade Primary Students” was developed in 2023 by the School of Mathematics at the Costa Rica Institute of Technology (ITCR in Spanish); its objective was to create a digital book covering the skills and content for that level as outlined in the official Costa Rican Mathematics program. In the initial stage of book creation, a thorough analysis of texts from three Costa Rican publishers was conducted. This evaluation was focused on the adequacy of figurative representations of geometric concepts, distractions in structuring and orientation, and the suitability of images of real objects. Considering the identified weaknesses, the digital resource was developed and subsequently validated through expert judgment. The result is an interactive geometry book characterized by the inclusion of figures in non-standardized positions in terms of structure and orientation, and a high percentage of real images, enhancing students’ spatial visualization and comprehension skills. Furthermore, the project encourages learning through dynamic representations by incorporating videos and interactive web applications.